Reviews - Julie J. Nichols; Charles Suhor; Edward Sullivan (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Reviews Julie J. Nichols - Meaning and The Evolution of Consciousness: A Retrospective on the Writing of Owen Barfield Charles Suhor - The Great Transfonnation: The Beginnings of Our Religious Traditions Charles Suhor - The Chalice and the Blade Edward Sullivan - The Art of Learning: An Inner Journey to Optimal Performance